Forecasting Commodity Price of Cayenne Pepper (Capsicum Frutescens L.) in Jember with Holt-Winters Exponential Smoothing Method to Get Financial Benefit - Muhammad Hanif Fadloli; R. Abdoel Djamali (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Cayenne pepper is one of the largest horticultural crop commodities produced in Jember Regency. Cayenne pepper has a high economic value and is in great demand by the people of Jember Regency, but the commodity price of cayenne pepper has a pattern of sharp fluctuations. The purpose of this research is to predict the price and identify the factors that influence the price of cayenne pepper in Jember Regency. This research is included in the type of quantitative descriptive research that uses the Holt-Winters Exponential Smoothing method as forecasting and the simple regression method as a determinant of the factors that influence prices. The results of this study are the most optimal forecasting parameter values, namely the alpha (????) value of 0.5, beta (β) of 0 and gamma (γ) of 0.22, and produce a MAPE value of 34%. Factors that affect changes in the price of cayenne pepper in Jember Regency are the price of substitute ingredients (red chilies) and rainfall.